Research on the Bearing Load Measurement Method Based on the Fusion of Redundant Strain Data and Jacking Data - Chengwei Fang; Aihua Liu; Hanhua Zhu; Yibin Deng (Applied Sciences)
To improve the accuracy of bearing load measurement in propulsion shafting, a bearing load measurement method based on redundant strain and jacking data fusion is proposed. Firstly, to address the issue of low measurement accuracy in strain gauge methods (SGM), a redundant strain gauge method (RSGM) is introduced to enhance the precision of strain-based measurements. Secondly, synchronize the measurement of strain data during the jacking phase and fuse the measurement data from the jacking phase based on the Bayesian estimation method to enhance the measurement accuracy of the jack-up method (JM). Lastly, the pre-decision results of the two types of measurement data are integrated at the decision level to obtain the final measured load. Simulation experiments have verified the correctness and applicability of the proposed measurement method. The research results indicate that, compared to the SGM, the RSGM offers higher measurement precision; the fusion measurement method can achieve more accurate results than the JM and RSGM under different bearing support conditions and jack-up scenarios.